High‐pressure processing of persimmon purée: Stability during chilled storage - Rodriguez, Anabel; Cap, Mariana; Ramos, Nelsi; Godoy, Maria Fernanda; Mascheroni, Rodolfo H.; Vaudagna, Sergio Ramon (Wiley, 2020)
The aim of the study was to evaluate the effect of the high pressure (HP) technology on the preservation of persimmon purée during chilled storage (1, 30, and 90 days at 4 ± 1 °C). Results showed that the treatment at 400 MPa for 1 min was enough to eliminate the microbial counts and no regrowth was observed during storage. Physicochemical parameters, phenolic compounds, and antioxidant capacity were not affected by HP and were kept stable during storage. The mechanical and rheological properties were not affected by HP treatments at 500 and 600 MPa, preserving these properties during storage. The HP treatments were not able to effectively preserve the chromatic parameters and achieve the complete inhibition of the enzyme´s activity. The conditions that achieved the best preservation of the quality properties was 600 MPa for 5 min.